ON CERTAIN MISDEMEANOR PROVISIONS IN THE LAW ON TAX PROCEDURE AND TAX ADMINISTRATION - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Certain acts in the Republic of Serbia foresee a wide range of tax misdemeanors. These are not only misdemeanors prescribed by the Law on Tax Procedure and Tax administration, but also misdemeanors contained in other laws. In the current Law on Tax Procedure and Tax Administration there are some specific misdemeanor provisions which will be the subject of this paper.